Aflatoxin contamination of milk and dairy feeds in the Greater Addis Ababa milk shed, Ethiopia - Gizachew, D.; Szonyi, Barbara; Tegegne, Azage; Hanson, Jean; Grace, Delia (Elsevier, 2016)
Aflatoxin B1 (AFB1) is a highly toxic metabolite of Aspegillus fungi that can contaminate animal feed. Cows that consume AFB1-contaminated feed excrete aflatoxin M1 (AFM1) in their milk. The aim of this study was to detect and quantify the amount of AFM1 in raw cow's milk and AFB1 in dairy feed samples in the Greater Addis Ababa milk shed using a value chain approach. For this purpose, 100 milk samples from dairy farmers and ten milk samples from milk traders were collected. In addition, 114 feed samples from dairy farmers and 42 feed samples from feed producers, processors and traders were collected. Analysis for AFM1 and AFB1 were conducted by a commercial enzyme-linked immunosorbent assay (ELISA). Results showed the presence of AFM1 in all milk samples, and contamination level ranged between 0.028 and 4.98 μg/L. Overall, only nine (8.2%) out of a total of 110 milk samples contained less than or equal to 0.05 μg/L of AFM1. Furthermore, 29 (26.3%) milk samples exceeded 0.5 μg/L. All the feed samples were contaminated with AFB1 ranging between seven and 419 μg/kg. Overall, out of a total of 156 feed samples collected, only 16 (10.2%) contained AFB1 at a level less than or equal to 10 μg/kg. At the same time, 41 (26.2%) of the feed samples contained AFB1 at a level exceeding 100 μg/kg. All dairy farmers used concentrate feed daily, which commonly included the mixture of wheat bran and noug (Guizotia abyssinica or Niger seed) cake (a byproduct from noug oil factories). Analysis of individual wheat bran and noug cake samples revealed that the contamination levels of AFB1 for wheat bran and noug cake were nine to 31 μg/kg and 290–397 μg/kg, respectively. Linear regression revealed significant associations between the presence of noug cake in the feed and the levels of contamination of both AFM1 in milk and AFB1 in feed. The level of aflatoxin contamination found in this study in milk and feed should prompt action to identify suitable interventions. These results suggest that risk mitigation should focus on noug cake to effectively reduce aflatoxin contamination in peri-urban dairy value chains in Ethiopia. Risk assessment of aflatoxins in noug seed and its by-products in other food chains is also warranted.